Integrating Jawi Language curriculum and character education in Thai Primary Schools: A qualitative case study - Wanida Salaeh; Ammar Salem Khan (EDUCARE Journal of Primary Education, 2025)
The lack of effective integration between the Jawi language curriculum and character education in Thai primary schools; challenges in teachers’ pedagogical adaptation; limited contextual learning materials; difficulties in students’ internalization of character values; the role of teacher autonomy and institutional support in implementation; the influence of socio-cultural context and community involvement on the sustainability of character education. This qualitative single-case study at Santiwitiya School, Thailand, examined Jawi curriculum integration in character education. Data were collected via classroom observations, interviews with principal, teacher, and student, and document analysis, then thematically analyzed using an interactive model, with trustworthiness ensured through triangulation, member checking, and ethical procedures. The findings indicate that Jawi-based character education at Santivitiya School is influenced by curriculum institutionalization, teacher autonomy, pedagogical capacity, and socio-cultural context. Lesson plans and worksheets ensure consistency but may limit flexibility. Effective character formation requires teacher autonomy, institutional support, community involvement, and active, contextual learning to address linguistic challenges. This study highlights the importance of balancing curriculum standardization with teacher autonomy and socio-cultural engagement, providing insights for effective Jawi-based character education and informing policy, pedagogy, and community collaboration.